Natural gum reduced/stabilized gold nanoparticles for drug delivery formulations - Dhar, Sheetal; Reddy, E. Maheswara; Shiras, Anjali; Pokharkar, Varsha; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2008)
``Gellan Gum'', widely used in food and confectionary industry as a thickening and gelling agent, has been employed as a reducing and stabilizing agent for the synthesis of gold nanoparticles. These nanoparticles display greater stability to electrolyte addition and pH changes relative to the traditional citrate and borohydride reduced nanoparticles. Subsequently these have been used to load anthracycline ring antibiotic doxorubicin hydrochloride. The drug loaded on these nanoparticles showed enhanced cytotoxic effects on human glioma cell lines LN-18 and LN-229.
Keywords: Apoptosis; Cytotoxicity; drug delivery; Gold; Nanostructures; natural gums

Cytotoxicity of sophorolipid-gellan gum-gold nanoparticle conjugates and their doxorubicin loaded derivatives towards human glioma and human glioma stem cell lines - Dhar, Sheetal; Reddy, E. Maheswara; Prabhune, Asmita; Pokharkar, Varsha; Shiras, Anjali; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Biocompatible gold nanoparticles were synthesized by using a naturally occurring gum-Gellan Gum-as a capping and reducing agent. These were further conjugated with sophorolipids which again were accessed through a biochemical transformation of a fatty acid. The cellular uptake of sophorolipid-conjugated gellan gum reduced gold nanoparticles and their cytotoxicity on human glioma cell line LN-229 and human glioma stem cell line HNGC-2 were investigated. Quite surprisingly even the simple sophorolipid-conjugated gellan gum reduced/capped gold nanoparticles showed greater efficacy in killing the glioma cell lines and, gratifyingly, the glioma stem cell lines also. The cytotoxic effects became more prominent once the anti cancer drug doxorubicin hydrochloride was also conjugated to these gold nanoparticles.